KONGRUENSI IDEMPOTENT-SEPARATING MAKSIMUM PADA p-SEMIGRUP REGULER - , FITRIANI, S.SI, Prof. Dr. Sri Wahyuni , M.S ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Semigroup is a structure with a associative binary operation. Since semigroup may not have an identity element and invers element, there is a regularity characteristic of element in semigroup. If all of the element of semigroup have regularity, then this semigroup is called regular semigroup. ï-regular semigroup is one of the class regular semigroups. It is a pair of regular semigroup with the set of idempotent elements which satifies some axioms. If the first axiom in the definition of ï-regular semigroup which explained about commutative law for idempotent elements leaving out, then a new class of regular semigroup is defined, called p-regular semigroup. In this case, the set of all ï-regular semigroups is subset of the set of all p-regular semigroup. After observing the characteristic of p-regular semigroup, define a maximum idempotent-separating congruence in p-regular semigroup. This congruence is the same congruence in the pair of orthodox and band. Finally conclusion, p-regular semigroup is a generalized regular semigroup (orthodox) which has the maximum idempotent-separating congruences.